MODEL AND METHOD OF ASSESSING THE MEDICAL DATA SUFFICIENCY - MOSKALENKO, Artem; OSYADLYI, Vitaliy (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The conducted state-of-the-art on known decisions on the use of blockchain technologies in the construction of information technology for medical data management showed that, despite a large number of different solutions, effective methods and solutions for medical data management based on blockchain technologies are currently lacking. Thus, improving the efficiency of medical data management by developing methods of medical data management based on blockchain technologies is currently an urgent problem. The aim of this study is to improve the efficiency of medical data management by developing a method for assessing the sufficiency of medical data before placing them in the blockchain.Models of blockchain block, blockchain fragment and blockchain node, presented in formalized form, as well as models of medical data management process (data sufficiency assessment) are developed, which are the theoretical basis for developing a method of assessing the medical data sufficiency.Rules for determining the sufficiency of medical data have been developed., which provide analysis of medical data in order to find all the predetermined necessary elements of medical data; to decide on the sufficiency or insufficiency of information; output of visualized hints, which data elements are missing, to ensure the ability to quickly add data; quantitative assessment of the sufficiency of medical data.The paper developed a method for assessing the sufficiency of medical data, which provides: the ability to analyze a variety of medical data for their sufficiency; the ability to quantify the sufficiency of medical data; in case of insufficiency of medical data in the set, formation of recommendations on supplementing the set of medical data – as a guide, what information should be added to the set of medical data to be able to download them to the section "Block data" of blockchain.
Keywords: blockchain technology; blockchain block; blockchain block section; medical data; medical data sufficiency